Endometrial hyperplasia and an occult ovarian tumor - Pereira,Sofia (2022)
Abstract Endometrial hyperplasia (EH) is a frequently found in postmenopausal women. Cases of recurrence are seen in women with multiple risk factors, unopposed estrogen therapy, and in estrogen-secreting tumors. Granulosa cell tumors of the ovary are a rare malignant type of estrogen-secreting tumor, usually presenting as a pelvic mass. In this report, we present the case of a 68-year-old asymptomatic woman submitted to total hysterectomy and bilateral salpingo-oophorectomy due to recurrent EH. Histology found an adult granulosa cell tumor of the ovary. This case aims to highlight that, although very rare, the presence of an estrogen-secreting tumor should be considered.